2011
DOI: 10.1007/s00125-011-2150-4
|View full text |Cite|
|
Sign up to set email alerts
|

Atlantic Diabetes in Pregnancy (DIP): the prevalence and outcomes of gestational diabetes mellitus using new diagnostic criteria

Abstract: GDM prevalence is higher when using newer IADPSG, compared with WHO, criteria, and these women and their offspring experience significant adverse pregnancy outcomes. Higher rates of GDM pose a challenge to healthcare systems, but improved screening provides an opportunity to attempt to reduce the associated morbidity for mother and child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
195
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(214 citation statements)
references
References 18 publications
13
195
0
6
Order By: Relevance
“…In group B, significantly more women had developed complications (70 %) as compared to women of group A who were [15]. Another study conducted by O'Sullivan et al observed significant association between GDM and 50, 250, and 30 times increased incidence of preeclampsia, polyhydramnios, and cesarean section rates, respectively [16].…”
Section: Discussionmentioning
confidence: 93%
“…In group B, significantly more women had developed complications (70 %) as compared to women of group A who were [15]. Another study conducted by O'Sullivan et al observed significant association between GDM and 50, 250, and 30 times increased incidence of preeclampsia, polyhydramnios, and cesarean section rates, respectively [16].…”
Section: Discussionmentioning
confidence: 93%
“…po valgio -< 6,7 mmol/l. Į tyrimą įtrauktų pacienčių charakteristikos buvo panašios į kitų Lietuvoje -VUL SK Centro filiale, VMKL Akušerijos ir ginekologijos klinikoje, LSMU ligoninės Kauno klinikose -ir Europoje -"Hyperglycemia and Adverse Pregnancy Outcomes" (HAPO), "Atlantic Diabetes in Pregnancy" (DIP) studijų tirtų moterų duomenis [9][10][11][12]. Lyginant su A. Duran ir bendraautorių atliktu tyrimu, kuriame tirtos Ispanijoje gyvenančios nėščiosios, mūsų tiriamosios buvo jaunesnės bei didesnis moterų skaičius turėjo antsvorio ar buvo nutukusios [13].…”
Section: Diskusijaunclassified
“…Nėščiųjų hipertenzijos ir preeklampsijos procentas pasiekė HAPO studijoje pateiktus hipertenzijos ir preeklampsijos rodiklius [11]. Tuo tarpu polihidramnionas diagnozuotas dvigubai dažniau, palyginti su DIP studija [12]. Pavėluota ND diagnostika bei dažnos šlapimo takų infekcijos, kurios nėštumo metu diagnozuotos beveik pusei tiriamųjų, galėjo lemti dažnesnį polihidramniono pasireiškimą.…”
Section: Lentelė Pagrindinės Tiriamųjų Charakteristikos Ir Nėščiųjų unclassified
See 2 more Smart Citations